2020
DOI: 10.3390/ijms21197204
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Cyanobacterial Metabolism as a Key to Efficient Biopolymer Production in Photosynthetic Microorganisms

Abstract: Cyanobacteria are photoautotrophic bacteria commonly found in the natural environment. Due to the ecological benefits associated with the assimilation of carbon dioxide from the atmosphere and utilization of light energy, they are attractive hosts in a growing number of biotechnological processes. Biopolymer production is arguably one of the most critical areas where the transition from fossil-derived chemistry to renewable chemistry is needed. Cyanobacteria can produce several polymeric compounds with high ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 125 publications
(215 reference statements)
0
14
0
Order By: Relevance
“…Related metabolic processes in bold in medium-color boxes. Critical enzymes in light- Various studies suggest that there are important interrelations between the PHA biosynthetic pathway and those of the central carbon metabolism [46], especially the glycogen pathway, one of the major cellular carbohydrate forms in cyanobacteria, which is degraded to a simpler compound: glucose. Dutt and Srivastava [47] showed that in PHA accumulating microalga photosynthetically grown under N-depletion, up to 87% of the carbon in PHB is derived from intracellular carbon reserves rather than from the CO2 fixed during the cultivation, but it was not clear which specific metabolic routes related with carbon fixation provided precursors for PHA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Related metabolic processes in bold in medium-color boxes. Critical enzymes in light- Various studies suggest that there are important interrelations between the PHA biosynthetic pathway and those of the central carbon metabolism [46], especially the glycogen pathway, one of the major cellular carbohydrate forms in cyanobacteria, which is degraded to a simpler compound: glucose. Dutt and Srivastava [47] showed that in PHA accumulating microalga photosynthetically grown under N-depletion, up to 87% of the carbon in PHB is derived from intracellular carbon reserves rather than from the CO2 fixed during the cultivation, but it was not clear which specific metabolic routes related with carbon fixation provided precursors for PHA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Though the physiological role of PHB is still largely unclear, recent studies suggest a function of PHB as an electron sink during unbalanced conditions and as an additional carbon storage to prevent a metabolic spillover (Koch and Forchhammer, 2021 ). This complex relationship links PHB synthesis and utilization to central metabolic pathways (Ciebiada et al, 2020 ; Koch et al, 2020b ). Therefore, the transcriptomic changes might not fully represent the effects of KaiAB1C1 and RpaA deficiency for cellular night- and daytime functions, which led us to analyze the metabolic changes in the two corresponding mutants.…”
Section: Resultsmentioning
confidence: 99%
“…PHB synthesis depends on many factors, such as the C:N ratio and nutrient starvation. A complex relationship links PHB synthesis and utilization to central metabolic pathways (Ciebiada et al, 2020;Koch et al, 2020). Therefore, the transcriptomic changes might not fully represent the role of KaiAB1C1 and RpaA in cellular nightand daytime functions, which led us to analyze the metabolic changes in the two corresponding mutants.…”
Section: Phb Accumulation Is Reduced In Synechocystis 6803 Kaiab1c1 and Rpaa Mutantsmentioning
confidence: 99%